FIFA 11+ prevention programme in preventing anterior cruciate ligament injury among soccer players: a scoping review - Munajat, Munayati; Azhar, Noor Izzati; Che Othaman, Nor Nazihah; Zainuddin, Siti Zulaikha; Justine, Maria; Kamarulzaman, Mohd Fadli; Bukry, Saiful Adli (Fakulti Perubatan dan Sains Kesihatan, UPM, 2022)
Soccer players are highly exposed to injuries due to the nature of the sport. Knowing the preventive measures of injury in soccer players is therefore crucial. FIFA 11+ improves the neuromuscular properties of the stabilising mus- cles of the joints. Numerous studies have generally investigated the effects of FIFA 11 +, however, evidence for ACL injury prevention is still limited. Therefore, this review aims to investigate the effects of FIFA 11+ as the ACL injury prevention programme among soccer players. Online databases (ScienceDirect, Springer, Scopus, Web of Science, PubMed, and Google Scholar) were used in the search for relevant publications. The quality of the literature was assessed using the Critical Assessment Score System of the Physiotherapy Evidence Database (PEDro) for randomised controlled trial papers. Twelve articles showed a consistent and positive effect of FIFA 11+ on reducing injuries among soccer players. Four studies showed its significant effect on knee strength and balance, two studies discussed on biomechanical performance, while six studies provided information on FIFA 11+ with exposure to ACL injuries after long-term training. Implementing the FIFA 11 + programme in the intervention group positively reduced expo- sure to ACL injury, with improved strength, balance, and biomechanical performance.